2019
DOI: 10.31202/ecjse.575642
|View full text |Cite
|
Sign up to set email alerts
|

Solarmeter Design for High Solar Radiation Measurement and Experimental Validation

Abstract: In this study, a solar meter was designed to measure high solar radiation. The solar meter uses the characteristic properties of a solar cell in order to measure solar radiation. In this way, measurements can be carried out without any limitations. The solar radiation equation was entered into the ARDUINO microcontroller in the solar meter, and the results were compared through another commercial solar meter. These results were entered into STATGRAPHIC software and three different functions with high regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Microcontrollers are used in different tasks such as fuel consumption [19], temperature control [3], water level control [15], electromagnetic valve control [21], solar radiation measure [22], driver control system [23] and solid fuel combustion capacity [24]. Sagouong and Tchuen [19] developed a microcontroller-based system to reduce fuel consumption to determine which of the three heat systems widely used in the Cameroon region is the most efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Microcontrollers are used in different tasks such as fuel consumption [19], temperature control [3], water level control [15], electromagnetic valve control [21], solar radiation measure [22], driver control system [23] and solid fuel combustion capacity [24]. Sagouong and Tchuen [19] developed a microcontroller-based system to reduce fuel consumption to determine which of the three heat systems widely used in the Cameroon region is the most efficient.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Koluman et al (2013) reported that animals are easily stressed in barns where solar radiation is directly effective, so some structural precautions should be taken. Solar radiation is measured by a device called pyranometer, and the accuracy and precision of this measurement are the most critical parameters in efficiency calculations (Ergün et al, 2019). Many studies were carried out to develop devices that can be used to measure solar radiation.…”
Section: Introductionmentioning
confidence: 99%